Triple-Gene Therapy for Stroke: A Proof-of-Concept in Vivo Study in Rats - Sokolov, Mikhail E.; Bashirov, Farid V.; Markosyan, Vage A.; Povysheva, Tatyana V.; Fadeev, Filip O.; Izmailov, Andrey A.; Kuztetsov, Maxim S.; Safiullov, Zufar Z.; Shmarov, Maxim M.; Naroditskyi, Boris S.; Palotás, András; Islamov, Rustem R. (Frontiers in Pharmacology, 2018)
Natural brain repair after stroke is extremely limited, and current therapeutic options are even more scarce with no clinical break-through in sight. Despite restricted regeneration in the central nervous system, we have previously proved that human umbilical cord blood mono-nuclear cells (UCB-MC) transduced with adenoviral vectors carrying genes encoding vascular endothelial growth factor (VEGF), glial cell-derived neurotrophic factor (GDNF) and neural cell adhesion molecule (NCAM) successfully rescued neurons in amyotrophic lateral sclerosis and spinal cord injury. This proof-of-principle project was aimed at evaluating the beneficial effects of the same triple-gene approach in stroke. Rats subjected to distal occlusion of the middle cerebral artery (MCA) were treated intrathecally with a combination of these genes either directly or using our cell-based (UCB-MC) approach. Various techniques and markers were employed to evaluate brain injury and subsequent recovery after treatment. Brain repair was most prominent when therapeutic genes were delivered via adenoviral vector- or UCB-MC-mediated approach. Remodeling of brain cortex in the stroke area was confirmed by reduction of infarct volume and attenuated neural cell death, depletion of astrocytes and microglial cells, and increase in the number of oligodendroglial cells and synaptic proteins expression. These results imply that intrathecal injection of genetically engineered UCB-MC over-expressing therapeutic molecules (VEGF, GDNF and NCAM) following cerebral blood vessel occlusion might represent a novel avenue for future research into treating stroke.